Empowerment of Marginalized Group through Rural Women's School - Noventi, Ike Arni (Jurnal Ilmiah Administrasi Publik, 2021)
Women as marginal groups have a large number in Indonesia. Women, especially in the rural area, generally have very limited knowledge and skills and they become more marginalized. Actualy they can become potential in national development if empowered. This research tries to describe the process of rural women empowerment in rural women’s school. Using descriptive research methods and qualitative approaches, this research focused on women's empowerment activities, learning systems, involved stakeholders and barriers faced by rural women's schools. The results of the study showed that empowerment activities were carried out by giving motivation, knowledge and skills. Learning system conducted through method of giving material, practice, and outclass. Stakeholders involved in running the schools are government, private sector, community and university. The obstacles in the implementation of this school are the fluctuating number of participants, limited funding, communication, and adjustment material training due to the absence of presenters.